PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PERUSAHAAN LISTRIK NEGARA AREA PEKANBARU - Sapitri, Ranty; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aimed to analyze the Influence of Organizational Commitment on Employee Performance Pekanbaru Area National Electricity Company. In this research there are two variables: Organizational Commitment ( X ) Employee Performance ( Y ) in which the population of this study were all employees remain part of the state electricity company offices Pekanbaru area with lots of samples is 76 respondents who use census techniques. Analysis of the data in this study using SPSS. The results of this study indicate that the organizational commitment consisting of affective commitment, continuance commitment and normative commitment owned National Electricity Company employees Pekanbaru Area. And the high performance owned National Electricity Company employees Pekanbaru Area. In this research, organizational commitment and significant positive effect on employee performance Pekanbaru Area National Electricity Company.Keywords : Affective commitment, Continuing Commitment, Normative Commitment and Employee Performance